Systematic literature review on current instruments of Indonesian information technology-based ELT materials development - Ikhsanudin, Ikhsanudin; Putri, Tri Cantika; Puspitasari, Nurwinda Laili; Ulyasari, Nur (UPT Bahasa Universitas Tanjungpura, 2025)
This study presents a systematic literature review (SLR) employing the PRISMA framework to analyse the development and evaluation of English Language Teaching (ELT) materials in Indonesia between 2016 and 2023. From an initial pool of 1,263 records, 24 studies were included following a rigorous screening process. The findings indicate a growing emphasis on IT-based materials, which accounted for 50% of the studies reviewed. Evaluation practices were observed in 79% of the studies, with 81% of these employing instruments, of which 52% were validated. Validation methods predominantly involved qualitative expert reviews and focus group discussions, underscoring the need for broader adoption of robust quantitative approaches. Despite progress, research remains limited on non-IT-based materials and the application of advanced validation techniques. This study highlights the importance of enhancing evaluation practices and aligning ELT material development with contemporary educational demands. It offers valuable insights for researchers, educators, and policymakers committed to advancing language education in Indonesia. How to cite this paper: Ikhsanudin, Putri, T. C., Ulyasari, N., & Puspitasari, N. L. (2025). Systematic literature review on the current instruments of Indonesian information technology-based ELT materials development. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(1), 146